Fetal Mummification in a Doe: A Case Report - Uttam Kumar Sahu, Uttam Kumar Sahu; Pooja, Kiran Singh; Nivetha P, Nivetha P; Brijesh Kumar , Brijesh Kumar; Khan, M H (The Indian Journal of Animal Reproduction, 2024)
This case report describes resolving a case of fetal mummification in a doe with a single fetus at 105±12 days of gestation. A 3.5 years old pleuriparous, non-descript pregnant doe was presented to the Referral Veterinary Polyclinic, IVRI Izatnagar. The case was diagnosed as fetal mummification after the delivery of a dead mummified fetus after medical treatment and manual intervention.